Spinopelvic Alignment Parameters in Spondylolisthesis Patients Compared to Nonspondylolisthesis Patients - Alijani, Babak; Ramzannejad, Armin; Yousefzadeh-Chabok, Shahrokh; Behzadnia, Hamid; Emamhadi, Mohammadreza; Davoudi-Kiakalayeh, Ali; Bijani, Enayatollah (Indian Journal of Neurosurgery, 2019)
Objective We aimed at describing spin pelvic alignment features in patients with degenerative spondylolisthesis (DS), in comparison with other patients complaining of low back pain but no evidence of spondylolisthesis on standard standing lateral lumbosacral X-ray.Methods In this prospective descriptive study, patients with low back pain included in two groups of DS and non-DS patients, according to preoperative lumbosacral X-ray in standard standing lateral position. Patient’s demographic characteristics, as well as spinopelvic alignment parameters including pelvic incidence (PI), pelvic tilt (PT), sacral slope (SS), lumbar lordosis, and facet joint orientation, were collected. DS patients were compared with non-DS, age-matched control group.Results DS patients were significantly obese (p = 0.031) and had a high PI (56.39 ± 11.5), SS (38.28 ± 10.32), and PT (18.52 ± 9.11), (p = 0.00, 0.01, 0.04, respectively). Moreover, segmental lordosis at L2–L3, L3–L4, and L5–S1 levels demonstrated a significant increase (p < 0.05). Facet joints at L4–L5 level were located more sagittally (37.5 ± 7.07 vs. 40.71 ± 6.33).Conclusion PI, SS, and PT significantly increase in DS patients compared with non-DS group. Elevated segmental lordosis at high lumbar levels and sagittal orientation of facet joints were other features observed in DS patients.
Keywords: spondylolisthesis; spinopelvic; alignment; parameters; body mass index